Family, a solid foundation in the educational process in the hospital classrooms - Mendoza Carrasco, Mariella Victoria (2017)
From a psycho-pedagogical point of view, the influence of family support in the Teaching-Learning process of children who are pedagogically assisted in Hospital Classrooms is analyzed. The quality of the family nucleus is supported, as a  manager and promoter of talents and learnings of their own children, taking into account the diversity in the family, as an opportunity to support children in vulnerable health conditions to overcome their real situations in which they find themselves and be taken care in their learning process. There is a need of working together, in the hospital institution, where hospital teachers, educational assistants, family, health professionals, administrative professionals and the children’s environment, provide motivation, collaboration and attention to the diverse needs of admitted children, offering them the best climate and confidence from those involved, favoring their wellbeing, development of potential capacities, abilities and skills.